Ameliorating Effect of Oral Guggulsterone Administration in Imiquimod-Induced Psoriasis in Mice - Raghad A. Khaleel; Munaf H. Zalzala (Iraqi Journal of Pharmaceutical Sciences, 2018)
Psoriasis is a common chronic skin condition characterized by infiltration of inflammatory cells into the epidermis and altered keratinocyte differentiation.